0D/3D Cu(II)‐containing coordination complexes constructed from the N, O‐donor ligands: structural insights and anticancer activity. Issue 13 (2nd April 2020) - Wang, Jin‐Cai; Hu, Peng; Zhao, Rui‐Sheng; Li, Hui‐Ling; Xu, Zhi‐Chao; Guo, Fei
Abstract: Two novel coordination polymers based on Cu(II) ions as the metal nodes, Cu(pydc)(2, 2‐bpy)(DMF)n (1, H2 pydc=3, 5‐pyridinedicarboxylate, 2, 2‐bpy=2, 2‐bipyridine) and [Cu(H2 O)2 (H2 imdc)2 ](H2 O)n (2, H3 imdc=1H‐imidazole‐4, 5‐dicarboxylic acid) have been synthesized via the hydrothermal or solvothermal conditions and characterized by techniques of elemental analysis, powder X‐ray diffraction (PXRD) as well as the analysis of single‐crystal X‐ray diffraction. Furthermore, the anti‐tumor activities of compounds 1 and 2 against on U251 brain glioma cells were evaluated in vitro . The Cell Counting Kit‐8 (CCK‐8) detection was performed to assess anti‐tumor activities of compounds 1 and 2 on U251 brain glioma cells. The Annexin V‐FITC/PI approach and Terminal deoxynucleotidyl transferase mediated dUTP nick‐end labeling (TUNEL) staining was used to determine the U251 brain glioma cells apoptosis after compounds treatment. Besides, the ROS assay was utilized to determine the ROS accumulation within U251 brain glioma cells after compounds treatment. The RT‐PCR was conducted to measure the ROS related genes relative expression. Abstract : Two Cu(II)‐containing coordination polymers have been constructued from the N, O‐bifunctional ligand via the hydrothermal or solvothermal conditions and characterized by techniques of elemental analysis, powder X‐ray diffraction (PXRD) as well as the analysis of single‐crystal X‐ray diffraction. Furthermore, the anti‐tumor activities of the as‐prepared Cu(II) coordination polymers were evaluated via the Cell Counting Kit‐8 assay, ROS assay and RT‐PCR.